The Impact of Car-Sharing on the Willingness to Postpone a Car Purchase: A Case Study in Hangzhou, China - Ying Hui; Yujiao Wang; Qinlu Sun; Lei Tang (Journal of Advanced Transportation)
This paper aims to explore the potential of car-sharing in reducing car ownership and what are the impact factors. Based on the data of Hangzhou “Fun Car-sharing” system, a discrete choice model was established to study the willingness to postpone car purchase with participation in car-sharing. Compared with previous studies, this study included the variables involved in the questionnaire and those related to the usage characteristics extracted from rental data and GPS data. The questionnaire data indicate that about 50% of respondents will postpone car purchase by participating in car-sharing. The discrete choice model indicates that car-sharing in China can play a role in delaying car purchase. The results further suggest that respondents who use car-sharing more frequently, travel to work by car, or have an activity anchor in their trip are more likely to postpone car purchase. Moreover, respondents whose most common travel purpose of car-sharing is work-related or car purchase plan is definite are less likely to postpone car purchase after participating in car-sharing. The insights gained in this study can help cities and car-sharing operators to formulate relevant policies and regulation that optimally integrate car-sharing services into the overall urban transport systems.